Innovation shortfalls - Rodríguez-Clare, Andrés 1993- (The World Bank, 2007)
There is a common perception that low productivity or low growth is due to what can be called an "innovation shortfall," usually identified as a low rate of investment in research and development (R&D) when compared with some high innovation countries. The usual reaction to this perceived problem is to call for increases in R&D investment rates, usually specifying a target that can be as high as 3 percent of GDP. The problem with this analysis is that it fails to see that a low R&D investment rate may be appropriate given the economy's pattern of specialization, or may be just one manifestation of more general problems that impede accumulation of all kinds of capital. How can we know when a country suffers from an innovation shortfall above and beyond the ones that should be expected given the country's specialization and accumulation patterns? This is the question the authors tackle in this paper. First, they show a simple way to estimate the R&D gap that can be explained by a country's specialization pattern, illustrating it for the case of Chile. For this country they find that although its specialization in natural-resource-intensive sectors explains part of its R&D gap, a significant shortfall remains. Second, the authors show how a calibrated model can be used to determine the R&D gap that should be expected given a country's investment in physical and human capital. If the actual R&D gap is above this expected gap, then one can say that the country suffers from a true innovation shortfall